Plywood from Indian Timbers: Lagerstroemia parviflora (Lendi) - Shukla, K. S.; Shukla, L. N. (Indian Forester, 1989)
Suitability of Lagerstroemia parviflora (lendi) for veneering and plywood making has been reported. It does not offer any gluing problem and satisfactory glue bond can be obtained with P-F and U-F for making plywood. The species has been found suitable for making plywood for general purposes, marine plywood, preservative treated plywood, fire-retardant plywood, plywood for concrete shuttering works and for blockboards. It is also observed that preserving and fire-retardant chemicals viz., Copper-chrome-arsenic (CCA) and ammonium. Phosphatecopper sulphate-sodium dichromate do not adversely affect the glue bond on treatment of plywood. However, the species does not appear to be very easy to treat as higher concentrations of chemical solutions are required for obtaining the desired retentions of the chemicals. Lagerstroemia parviflora, therefore, could be included in the list of timber species suitable for above purposes in tbe relevant Indian Standards Specifications.